2014
DOI: 10.5812/jjm.9016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Achillea millefolium and Thymus vulgaris Extracts Against Newcastle Disease Virus in Ovo

Abstract: Background:Nowadays natural products such as pure compounds and plant extract scan provide unlimited opportunities for new antiviral drugs. Newcastle disease virus (NDV) is one of the most important viral diseases in poultry industry. Vaccination could provide protection against NDV outbreaks, but it is not sufficient because infections by NDVs have remained frequent around the world.Objectives:The current research aimed to study Achillea millefolium and Thymus vulgaris antiviral activity against Newcastle dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Focus of radiation protection has shifted to test the radioprotective potential of plants and herbs in the hope that one day it will be possible to find a suitable pharmacological agent (s) that could protect humans against the deleterious effects of ionizing radiation in clinical and other conditions. Previous studies on the extracts of ACM have reported antioxidant (Trumbeckaitea et al, 2011), antiviral (Rezatofighi et al, 2014), antispasmodic (Moradi et al, 2013) hepatoprotective (Yaeesh et al, 2006), gastroprotective (Potrich et al, 2010), immunological (Yassa et al, 2007) and antiinflammatory (Benedek et al, 2007) activities. Deoxyribonucleic acid (DNA) damage occurs either by direct ionization or indirectly through generation of free radicals that attack DNA, resulting in single-strand breaks and oxidative damage to sugar and base residues (Breen & Murphy, 1995), In this respect, γ-rays are exogenous DNA damaging agents cause a marked increase in micronuclei frequencies in the γ-irradiated group (for both mono-and binucleated cells) as shown in Table 1.…”
Section: Discussionmentioning
confidence: 94%
“…Focus of radiation protection has shifted to test the radioprotective potential of plants and herbs in the hope that one day it will be possible to find a suitable pharmacological agent (s) that could protect humans against the deleterious effects of ionizing radiation in clinical and other conditions. Previous studies on the extracts of ACM have reported antioxidant (Trumbeckaitea et al, 2011), antiviral (Rezatofighi et al, 2014), antispasmodic (Moradi et al, 2013) hepatoprotective (Yaeesh et al, 2006), gastroprotective (Potrich et al, 2010), immunological (Yassa et al, 2007) and antiinflammatory (Benedek et al, 2007) activities. Deoxyribonucleic acid (DNA) damage occurs either by direct ionization or indirectly through generation of free radicals that attack DNA, resulting in single-strand breaks and oxidative damage to sugar and base residues (Breen & Murphy, 1995), In this respect, γ-rays are exogenous DNA damaging agents cause a marked increase in micronuclei frequencies in the γ-irradiated group (for both mono-and binucleated cells) as shown in Table 1.…”
Section: Discussionmentioning
confidence: 94%
“…Haemaglutination activity (HA) was evaluated using allantoic fluid and egg infectious dose was calculated (10 -10.16 /ml EID5) as suggested by Rezatofighi et al (2014).…”
Section: Calculation Of Egg Infective Dose (Eid50) Of Virusmentioning
confidence: 99%
“…The standard dose was selected for virus, experimental plant extract and control. About 0.2 ml/egg (virus), 0.2 mg/0.2 ml for (N. sativa) and 20 µg/ml of the ribavirin was selected (Rezatofighi et al, 2014).…”
Section: Preparation Of Inoculumsmentioning
confidence: 99%
“…T. vulgaris was found to be effective against HSV-1/HSV-2 and NDV. Essential oils of this plant were able to disrupt viral envelopes and prevented attachment of the virion to the host cell (Rezatofighi et al, 2014).…”
Section: Thymus Vulgarismentioning
confidence: 99%